The 7th Asia-Pacific Transport Working Group (APTWG) meeting. (1st November 2017) - Ida, K.; Kong, D.F.; Fujita, T.; Ido, T.; Ko, W.H.; Maeyama, S.
Abstract: This conference report summarizes the contributions to, and discussions at, the 7th Asia-Pacific Transport Working Group Meeting held at Nagoya University, Japan, during 5–8 June 2017. The topics of the meeting were organized under four main headings: (1) turbulence and blob at the boundary of magnetic topology, (2) model reduction and experiments for validation, (3) mode competition in turbulence and MHD driven by energetic particle, (4) mechanism determining plasma flows and their impact on transport and MHD. The Young Researchers Forum which was held in this meeting is also described in this report.